Cholecystobronchocolic Fistula: A Late Complication of Biliary Sepsis - Collie, D. A. (Hindawi Publishing Corporation, 1994)
A case of a 48 year old woman presenting with bilioptysis due to a cholecystobronchocolic fistula is reported. Bilioptysis is a rare complication of biliary fistulae, with a high mortality due to chemical pneumonitis. Bronchospasm and rapid respiratory failure may ensue if aggressive management is not adopted. The site of fistulation is established by cholangiography, preferably by the percutaneous transhepatic route. Continued biliary drainage can lead to closure of these fistulae, or allow sufficient improvement in clinical condition to allow definitive surgery to be performed electively.